An Alien in the Group: Eusocial Male Bees Sharing Nonspecific Reproductive Aggregations. Issue 1 (30th October 2015) - dos Santos, C. F.; Ferreira-Caliman, M. J.; Nascimento, F. S.
Abstract : Sexual selection predicts that individuals competing for access to sexual partners should maximize their chances of mating by looking for sites where the chances of finding partners are more likely to occur. However, males of stingless bees have been observed sharing nonspecific reproductive aggregations. This uncommon behavior appears to confer no obvious increase of individual fitness. It has been suggested that this reproductive strategy is due to the similarity between male odors common to different stingless bee species. Cuticular hydrocarbons (CHCs) are candidate odors of interest because their nonvolatile pheromone nature allows them to play an important role in sexual behavior and species recognition. Here, we review the literature to evaluate whether any phylogenetic patterns exist among male stingless bees that aggregate with closely or distantly related species. We also compared the CHC profiles of males of Neotropical stingless bee species ( Plebeia sp. Schwarz, Trigona spinipes (F.), Tetragona clavipes (F.), Nannotrigona testaceicornis (Lepeletier), Scaptotrigona aff. depilis (Moure), Tetragonisca angustula (Latreille), and Melipona subnitida (Ducke) to reveal any chemical similarities among their male odors. We found males of 21 stingless bee species involved in interspecific interactions mainly from Neotropical and Indo-Malayan/Australasian regions. Alien males did not necessarily visit host aggregations of closely related species. Furthermore, the CHC profiles of different studied species were very distinct from each other and do not overlapped at all. It is unclear yet why this apparently nonadaptive behavior carried out by some stingless bee males.